If square root 3 minus 1 is a root of the equation 2x^2 - 2kx + 4=0 then k equals

Guest Nov 15, 2017

#1**+2 **

ax^{2 }+ bx + c = 0

To solve this problem, we need to use the formula X_{1}*X_{2 }= c ÷ a

(√3-1) * X_{2 }= 4 ÷ 2

X_{2 }= 2/ √3-1

Using that, we can figure out k,

Using this

X_{1 }+ X_{2 }= -a/b

(2/√3-1) + (√3-1) = -(-2k/2)

We got k = 2√3

Can someone check over my work? Not sure about the answer, pretty sure the solution is right...

supermanaccz
Nov 15, 2017

#1**+2 **

Best Answer

ax^{2 }+ bx + c = 0

To solve this problem, we need to use the formula X_{1}*X_{2 }= c ÷ a

(√3-1) * X_{2 }= 4 ÷ 2

X_{2 }= 2/ √3-1

Using that, we can figure out k,

Using this

X_{1 }+ X_{2 }= -a/b

(2/√3-1) + (√3-1) = -(-2k/2)

We got k = 2√3

Can someone check over my work? Not sure about the answer, pretty sure the solution is right...

supermanaccz
Nov 15, 2017